Rethinking Violence Prevention in Rural and Underserved Communities: How Veteran Peer Support Groups Help Participants Deal with Sequelae from Violent Traumatic Experiences. Issue 2 (15th March 2019) - Azevedo, Kathryn J.; Ramirez, Jeremy C.; Kumar, Anusha; LeFevre, Ann; Factor, Adam; Hailu, Elon; Lindley, Steven E.; Jain, Shaili
Abstract: Purpose: Access to mental health care and programs that address violence prevention can be a challenge for veterans residing in rural and underserved areas. A growing number of trauma‐affected veterans are now returning to rural areas upon completion of military service. The Palo Alto VA Health Care System has piloted a program known as the Peer Support Program (PSP) where certified peer support specialists hold group sessions for their fellow veterans in remote, community‐based outpatient clinics. Methods: A total of 29 peer‐support group participants and 1 certified peer specialist were interviewed. Semistructured interviews began with open‐ended questions regarding participant firsthand experiences with the support group setting. These were followed by direct questions that addressed the role of the PSP, expectations for the PSP, as well as benefits and limitations of the program. We performed a domain analysis using the Spradley ethnographic method on 325 pages of compiled narrative data focusing on violence‐related themes. Findings: Four key themes emerged, including: 1) Violence in Military Training Not Acceptable in Civilian Life, 2) Peer Support Creates the Trust to Speak Freely, 3) Skills Are Taught to Defuse Violence, and 4) The Veteran Peer Support Specialist Relationship Is Multi‐Dimensional. Conclusions: These emergent themes illustrate how trauma‐focused assistance rendered by peer support specialists as part of an interdisciplinary mental health team can be implemented to benefit trauma‐affected individuals and their communities in the prevention of future violence.